THE DEVELOPMENT OF A WEB-BASED LEARNING TO IMPROVE A CREATIVE WRITING ABILITY - Atikah Mumpuni; Laelia Nurpratiwiningsih (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
writing was considered as difficult by most of students due tue lack of a practice in materializing ideas into a writing language. Therefore, it was needed a writing learning that provides a medium for students to train materializing that ideas. This research was aimed to develop a web-based learning in form of learning devices that comprise of 1) syllabus; 2) Class Event Unit (SAP); web-based learning media dan 4) instrument of a feasible and effective creative writing assessment  in improving a student writing ability. This was a Research and Development (R&D) study method developed by  Borg and Gall. There were two results include: 1) product feasibility viewed from material expert assessment and student response that jointly assess good. 2) product effectiveness based on average improvement and difference of writing ability, a treatment-given group obtain a better result. A web-based learning developed was declared feasible and effective in improving a student creative writing ability